127k views
5 votes
Solve for the variable "d" in the following equation.


F=(Gm_1 m_2)/(d^2)

2 Answers

4 votes


F = (Gm_(1)m_(2) )/(d^(2) )

F x
d^(2) = G
m_(1)m_(2)


d^(2) =
(Gm_(1)m_(2))/(F)

d = ±
\sqrt{(Gm_(1)m_(2))/(F) }

User Marcelo Villa
by
6.1k points
6 votes

Since "m1" and "m2" represent different masses, we can change them to different letters. This will make it easier to solve.

m1 = m

m2 = n

F = G*m1*m2/d^2 → F = Gmn/d^2

Steps to solve for d:

F = Gmn/d^2

~Multiply d^2 to both sides

d^2 * F = d^2 * Gmn/d^2

~Simplify

d^2 * F = Gmn

~Divide F to both sides

d^2*F/F= Gmn/F

~Simplify

d^2 = Gmn/F

~Take the square root of both sides

√d^2 = ±√Gmn/F

~Simplify

d = ±√Gmn/F

Since we are done solving for d, we can input "m1" and "m2" to replace "m" and "n".

d = ±√Gmn/F → d = ±√G*m1*m2/F

Therefore, the answer is [ d = ±√G*m1*m2/F ]

Best of Luck!

User Mazen Harake
by
6.0k points